"Unico grande amore": AS Roma Supporters' Football Songs. (2nd January 2016) - Ricatti, Francesco
Abstract : This paper considers songs devoted to (and sung for) the football team AS Roma by its supporters. Some of these songs were written by the very famous Roman singer-songwriter Antonello Venditti, others by less famous authors and singers, and often simply by supporters, who created new lyrics to be sung at the stadium to the melodies of famous songs. Many of these songs can be described as love songs, suggesting that for many Romans there is no greater passion than that experienced and expressed for their football team. The article argues that Roma fans' absurd passion for their football team has profound political implications. The act of assigning certain specific emotions to individuals and groups through football events and related cultural productions, such as songs, is dependent upon relations of power. Particular emotions are central to the identity of specific groups and communities, and therefore become, in a broad sense, political. This is especially true when they are performed in mass gatherings such as football matches and celebrations. Football emotions, and therefore emotional songs about football, therefore give body to political beliefs, identities and values.